Effects of Chenpi (Citrus reticulata cv. Chachiensis) on serum antioxidant enzymes, inflammatory factors, and intestinal health in Beagle dogs - Wang, Wencan; Xu, Ling; Zhang, Yan; Cao, Yong; Yang, Yixue; Liu, Guo; Mao, Xin (Frontiers in Microbiology, 2025)
Ensuring companion animal welfare is a top priority for the pet industry and owners alike. The health of the pets can be directly and effectively improved through diet. Chenpi includes beneficial ingredients with proven anti-inflammatory, antioxidant, and immunomodulatory properties. The present investigation involved feeding snacks infused with Chenpi powder (CPP) to dogs for 42 days to examine the potential health benefits of CPP. The research evidenced a notable increase in serum superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activity in dogs, accompanied by a decrease in malondialdehyde (MDA), interleukin-8 (IL-8), and interferon-gamma (IFN-γ) level. Additionally, CPP increased fecal scores and significantly reduced fecal odors due to inhibition of 3-methylindole, hydrogen sulfide (H2S), and ammonia nitrogen (NH4+-N), and also raised the levels of fecal secretory immunoglobulin A (SIgA). Analysis of the microbial composition via 16S rRNA sequencing showed that CPP increased Bacteroidota and decreased Firmicutes in the gut flora at the phylum level. Functional prediction study of microbial communities also showed that the CPP group enriched metabolic and genetic information processing pathways. In addition, there were significant correlations between serum indicators and several significantly altered microorganisms. These findings suggest that CPP can potentially enhance the overall health of dogs by reducing fecal odorants, enhancing antioxidant and immunological capabilities, and modulating intestinal flora. This study establishes a solid scientific foundation regarding the application of CPP in functional pet foods.